Pengaruh Modal Kerja dan Kebijakan Pendanaan terhadap Profitabilitas pada Perusahaan Farmasi Periode 2019 – 2023 - Nur Fitriah Apriliana; Slamet Mudjijah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to determine the effect of cash turnover, receivable turnover, inventory turnover, and capital structure on profitability. The population in this study is 13 Pharmaceutical Companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The research sample was determined using a purposive sampling method, and there were 11 companies that met specified criteria. This study uses multiple linear regression method using the Statistical Package for the Social Sciences (SPSS) version 26 program. The results of this study indicate that Capital Structure have a negative effect on Profitability, and Cash Turnover, Receivable Turnover, and Inventory Turnover have no effect on Profitability.